Immunoglobulin A Nephropathy with Extracapillary Proliferation and Positive Anti-Neutrophil Cytoplasmic Antibodies: A Rare Cause of Dual Glomerulonephritis (2020)
ABSTRACT: The coexistence of immunoglobulin A (IgA) nephropathy and associated pauci-immune anti-neutrophil cytoplasmic antibody (ANCA) glomerulonephritis represents a rare concurrence of two common forms of glomerulonephritis; the pathogenesis, treatment, and prognosis of this dual glomerulopathy are not well described. This illustrative case can present this association in an HIV-positive patient and how despite the coexistence of these two entities, the patient had control of his kidney disease with low doses of steroids, contrary to the different reports of cases in the literature in which the treatment is often more aggressive. In this case report, we review the literature on this dual glomerulonephritis and confront clinical and treatment aspects regarding the different clinical cases reported in the databases.